ANALYSIS OF THE RESULTS OF GEOMONITORING HIGH-RISE BUILDINGS IN ASTANA CITY - Murat A., Мурат А.; Balakhmetova T., Балахметова Т. (Рroblems of engineering and professional education, 2023)
The article describes geodetic deformations of various buildings and structures. methods and methods of control are analyzed. Advantages and disadvantages of different methods draw conclusions about the shortcomings. As a result of observation of a high-rise building in Astana Based on the data obtained, the accuracy parameters and deformation elements were analyzed.